Mitochondrial DNA Promotes NLRP3 Inflammasome Activation and Contributes to Endothelial Dysfunction and Inflammation in Type 1 Diabetes - Pereira, Camila A.; Carlos, Daniela; Ferreira, Nathanne S.; Silva, Josiane F.; Zanotto, Camila Z.; Zamboni, Dario S.; Garcia, Valéria D.; Ventura, Dora Fix; Silva, João S.; Tostes, Rita C. (Frontiers in Physiology, 2020)
Background: NLRP3 inflammasome activation in response to several signals, including mitochondrial DNA (mDNA), regulates inflammatory responses by caspase-1 activation and interleukin-1β (IL-1β) release. Circulating mDNA is linked to micro and macrovascular complications in diabetes. However, a role for mDNA in endothelial dysfunction is not clear. We tested the hypothesis that mDNA contributes to diabetes-associated endothelial dysfunction and vascular inflammation via NLRP3 activation. Methods: Vascular reactivity, reactive oxygen species (ROS) generation, calcium (Ca2+) influx and caspase-1 and IL-1β activation were determined in mesenteric resistance arteries from normoglicemic and streptozotocin-induced diabetic C57BL/6 and NLRP3 knockout (Nlrp3-/-) mice. Endothelial cells and mesenteric arteries were stimulated with mDNA from control (cmDNA) and diabetic (dmDNA) mice. Results: Diabetes reduced endothelium-dependent vasodilation and increased vascular ROS generation and caspase-1 and IL-1β activation in C57BL/6, but not in Nlrp3-/- mice. Diabetes increased pancreatic cytosolic mDNA. dmDNA decreased endothelium-dependent vasodilation. In endothelial cells, dmDNA activated NLRP3 via mitochondrial ROS and Ca2+ influx. Patients with type 1 diabetes exhibited increased circulating mDNA as well as caspase-1 and IL-1β activation. Conclusions: dmDNA activates endothelial NLRP3 inflammasome by mechanisms that involve Ca2+ influx and mitochondrial ROS generation. NLRP3 deficiency prevents diabetes-associated vascular inflammatory damage and endothelial dysfunction. Our study highlights the importance of NLRP3 inflammasome in diabetes-associated vascular dysfunction, which is key to diabetic complications.